Function of metaphors in framing the global crisis - Miletić, Nikolina (Slavia Centralis, 2023)
Metaphors are often used in media discourse by journalists, epidemiologists and politicians as a means of persuasion and propaganda (cf. Zovko-Bošnjak 2018: 346). This paper aims to examine the use of metaphors in Croatian and German newspapers that address the global crisis caused by the pandemic, the war and inflation. The following research questions are addressed: Which metaphors are used most frequently? What is the function of metaphors in framing the global crisis? What are the interlingual differences in the use of metaphors in Croatian and German? The aim is to capture interlingual differences in the use of metaphors in the media discourse on pandemics, war and inflation.
Keywords: metaphors; framing; Croatian and German newspapers; discourse analysis